Quality of E-Book Teaching Materials with Scientific Inquiry Approach in Strengthening Science Literacy for Elementary School Students - Rokhayati, Istiqana Tri; Prasasti, Pinkan Amita Tri; Maruti, Endang Sri; Irawan, Nico (Universitas Muhammadiyah Mataram, 2022)
Currently the teaching materials used by teachers do not pay attention to the condition of students and their environment, because in general teachers still use conventional teaching materials as a guide in learning. This makes teachers very dependent on conventional teaching materials. This study aims to determine the quality of E-book teaching materials with a scientific inquiry approach in strengthening scientific literacy for elementary school students. This type of research is research and development (Research and Development) using the development model developed by Borg and Gall, and only taken 6 out of 10 overall stages. The subjects in this study were fourth grade elementary school students. The data collection instrument used in this study was a Likert scale questionnaire with qualitative descriptive and quantitative descriptive data analysis techniques. The results of expert validation research show that ebook teaching materials with a scientific inquiry approach can be said to be very feasible by experts according to the indicators of media feasibility, language feasibility, material feasibility. At the small-scale trial stage, the teaching materials developed also received a very good response from teachers and students. Thus the development of ebook teaching materials is expected to be an alternative learning so that concepts in science material can be conveyed properly and can strengthen scientific literacy in fourth grade elementary school students. The results of expert validation research show that ebook teaching materials with a scientific inquiry approach can be said to be very feasible by experts according to the indicators of media feasibility, language feasibility, material feasibility. At the small-scale trial stage, the teaching materials developed also received a very good response from teachers and students. Thus the development of ebook teaching materials is expected to be an alternative learning so that concepts in science material can be conveyed properly and can strengthen scientific literacy in fourth grade elementary school students. The results of expert validation research show that ebook teaching materials with a scientific inquiry approach can be said to be very feasible by experts according to the indicators of media feasibility, language feasibility, material feasibility. At the small-scale trial stage, the teaching materials developed also received a very good response from teachers and students. Thus the development of ebook teaching materials is expected to be an alternative learning so that concepts in science material can be conveyed properly and can strengthen scientific literacy in fourth grade elementary school students.